A robust blind signcryption scheme for secure internet of drones communication - Tahri Rachid; Abdellah Ouammou; Abdellatif Lasbahani; Hibat Eallah Mohtadi (Universitas Ahmad Dahlan, 2026)
The rapid deployment of the internet of drones (IoD) exposes aerial networks to authentication failures, eavesdropping, data theft, and impersonation attacks due to open wireless communication. This paper presents a lightweight identity based blind signcryption scheme for secure IoD communication. The scheme leverages hyper-elliptic curve cryptography to provide strong security with reduced computational overhead, making it suitable for resource-constrained drones. The blind signcryption mechanism enhances privacy by preventing the signer from accessing message content. Informal analysis shows that the scheme achieves confidentiality, authentication, anonymity, forward secrecy, and resis tance to common protocol-level attacks. Formal verification using the Scyther tool confirms secrecy, agreement, and authentication properties under a stan dard symbolic adversary model. Analytical and simulation-based evaluations demonstrate average reductions of 59.60% in computational cost, 48.86% in communication overhead, and 55.75% in energy consumption compared with existing schemes. While the results confirm protocol-level efficiency, real-world implementation and testbed validation remain future work.